Federated States of Micronesia : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2013)
The Federated States of Micronesia (FSM) is highly dependent on external aid. Following a recession in FY2006-08, the FSM economy has grown by 2-2 1\2 percent for FY2010 and FY2011. The economy remains dependent on the large public sector, although the fisheries and agriculture sectors have shown signs of growth. Despite some deterioration in current account balance, external balance also has sustained a stable flow of official transfers. However, economic growth is likely to slow in the near term owing to a decline in public sector demand.